Erg testing with the BioRowTech System - Kleshnev, V. (BioRow, 2019)
The main purpose of the BioRowTech system for the ergometer is to make technical improvements and receive immediate numerical feedback of these improvements. With the latest addition of the handle force sensor (1), the system can be used for comprehensive training and testing of rowers' performance and technique. In March, a test was conducted which included 42 junior rowers using the BioRowTech system: 23 male (average height 1.85 m, weight 80.6 kg) and 19 female (1.73 m, 67.2 kg) athletes. Each rower performed a 4 min test on a stationary rowing machine (Concept2-D) with racing force application and incremental increase of the stroke rate, which was targeted for each 1 min interval as follows: 20, 24, 28 and 32spm. Four variables were measured: positions of the handle, seat and trunk (with the BioRow string pots), and handle force (with the BioRow wired force sensor). The data was recorded directly to a computer, and then each 1 min sample was processed using the standard BioRow method (RBN 2017/12). After the testing, each rower received a one-page report (see an example in Appendix 1), and the coaches received summary tables, where rowers were ranked on the most important variables: stroke length, average force, work per stroke, Catch, Rowing Style and Finish factors, etc. The analysis below is quite descriptive: its main purpose is to help the rowers and coaches to understand the data better, though, as usual, I tried to get something new out of it. The difference of 7% in stroke length (1.61±0.10 m in males, and 1.50±0.08 m in females) can be fully explained by the difference in body height. The ratio of the stroke length to the body height was nearly the same: 87.1±3.2% in males, and (86.8±2.7% in females. The longest stroke length was found at 24spm (Fig.1), then it decreased by about 7 cm or 4% at 32 spm. Average force was about 20% higher in males (393N) than in females (314N), but relative to the body weight, the difference was only 5.4% (4.97 N/kg in males and 4.70 N/kg in females). Force increased with the stroke rate (Fig.2), and males increased it more significantly (by 8%) than females (by 4%). The shape of the force curve can be evaluated with the ratio of the average to the maximal force: 100% gives a perfect rectangular shape (practically impossible to achieve), 50% is a perfect triangular shape. The target value was set at 55% - a sort of "fat" triangle. On average, the shape of the force curve was the same (48.1%) in both males and females and didn't change much with stroke rate. Work per stroke WpS is the product of stroke length and force application. Average WpS in absolute values was 26% higher in males (727 J) than in females (532 J). Relative WpS as a ratio to body weight was 12.3% higher in males (9.05 J/kg) than in females (7.94 J/kg). At higher stroke rates, WpS was nearly constant in males (a shorter stroke length was balanced by a higher force), and slightly decreased in females (Fig.3). As it was found before (RBN 2018/02), Catch Factor CF is more negative on a stationary erg compared to the boat or a machine with a mobile stretcher. In this group, average CF was significantly more negative in females (-41±20 ms) than in males (-27±25 ms), which means that in general, the females started pushing the stretcher earlier before the catch, and spend more time on changing direction of the body mass movement at the catch. Average Rowing Style Factor RSF was found to be 67.6±12.3% in males and 71.3±11.7% in females: both values are quite far from the target value of 90%. This means that, in males, 32.4% of the handle movement during beginning of the drive (from catch to the "transition point") was contributed by upper body (target was set at 10% only), and in females, it was 28.7%. The main contribution was made by a too early "opening" the trunk (25.3% in males and 22.8% in females), and the rest came from "grabbing" of the arms and shoulders (7.1% in males and 5.9% in females). This means that the rowing style in this group of junior rowers requires significant improvement, and continuous use of the BioRowTech system would help to achieve it efficiently.